Gene expression, molecular docking, and molecular dynamics studies to identify potential antifungal compounds targeting virulence proteins/genes VelB and THR as possible drug targets against Curvularia lunata - Kamboj, Himanshu; Gupta, Lovely; Kumar, Pawan; Sen, Pooja; Sengupta, Abhishek; Vijayaraghavan, Pooja (Frontiers in Molecular Biosciences, 2022)
Curvuluria lunata is a melanized fungus pathogenic to both plants and animals including humans, causing mild, febrile, to life-threatening illness if not well-treated. In humans, it is an etiological agent of keratomycosis, sinusitis, onychomycosis in immunocompromised and immunocompetent patients. Development of multiple drug resistance strains poses a critical treatment issue as well as public health problem. Natural products are attractive prototypes for drug discovery due to their broad-spectrum efficacy and lower side-effects. The present study explores possible targets of natural antifungal compounds (α-pinene, eugenol, berberine and curcumin) against C. lunata via gene expression analysis, molecular docking interaction, and molecular dynamics (MD) studies. Curcumin, berberine, eugenol and α-pinene exhibited in-vitro antifungal activity at 78 µg/mL, 156 µg/mL, 156 µg/mL, and 1250 µg/mL, respectively. In addition, treatment by these compounds led to complete inhibition of conidial germination and hindered the adherence when observed on onion epidermis. Several pathogenic factors of fungi are crucial for its survival inside the host including those involved in melanin biosynthesis, hyphal growth, sporulation, and mitogen activated protein kinase (MAPK) signalling. Relative gene expression of velB, brn1, clm1 and pks18 responsible for conidiation, melanin, cell wall integrity was down-regulated significantly. Results of molecular docking possessed good binding affinity of compounds and has confirmed their potential targets as THR and VelB protein. The docked structures, having good binding affinity among all, were further refined, and rescored from their docked poses through 100 ns long MD simulations. MDS study revealed that curcumin formed stable and energetically stabilized complex with the target protein. Thereby, study concludes that compounds possess significant efficacy to inhibit the C. lunata growth targeting virulence proteins/genes involved in spore formation and melanin biosynthesis.